Case report: Opsoclonus-myoclonus syndrome associated with abdominal neuroblastoma - Águeda Sapiña; Adela Cañete; Tina Barahona; María Plasencia; María Moran; Olivia Prades; Davinia Fernandez; Laura Arjona; Paula Rubio; Jordi Bernabeu (Psicooncologia, 2012)
Opsoclonus-ataxia, also called “dancing eye syndrome,” is a serious neurologic condition that is often a paraneoplastic manifestation of occult neuroblastoma in early childhood. Although survival is high with anti-tumoral treatment and immunosuppressive therapy, outcome generally includes significant developmental and behavioral sequelae. We report a case diagnosed at nine month of age, treated in our Unit and refered for a multidisciplinary neuropsychological rehabilitation when she was 4 year old.